Study on Development Suggestions for the Key Parts Industry Chain of China’s New Energy Vehicles - Ding, Qian; Feng, Qianlong; Kang, Kai; Yang, Xianglu; Wu, Shuo; Zhang, Fan (International Journal of Global Economics and Management, 2024)
The development of new energy vehicles is the inevitable path for China’s automotive industry to transition from being a large player to a powerful one. This article focuses on analyzing the current development status of China’s automotive industry, particularly in the realm of new energy vehicles. It examines the domestic market situation and export competition landscape of new energy vehicles, further evaluating the current status of the new energy vehicle industry chain, technological situation, enterprise competition landscape, and the regional distribution pattern of core components. Finally, based on the problems existing in the development of the new energy vehicle industry chain, it puts forward targeted development suggestions.